Radiovesicolomics-new approach in medical imaging - Stępień, Ewa Ł.; Rząca, Carina; Moskal, Paweł (Frontiers in Physiology, 2022)
This review introduce extracellular vesicles (EVs) to a molecular imaging field. Based on the idea of omics, the usage of high-throughput methods to characterise the molecular content of a single biological system, vesicolomics seams to be the new approach to collect molecular data about EV content, to find novel biomarkers or therapeutic targets. The application of different imaging techniques, including those based on radionuclides as positron emission tomography (PET) or single photon emission computed tomography (SPECT), in combination of molecular data about EVs, opens the new space for radiovesicolomics – a new approach to be used in theranostics.